KEPEMILIKAN TANAH HAK MILIK OLEH WARGA NEGARA ASING YANG DIATASNAMAKAN WARGA NEGARA INDONESIA BERDASARKAN AKTA KONTRA LETTER - Theofillus Setiawan (Perpustakaan Universitas Surabaya, 2014)
Property rights of land ownership by foreign nationals are prohibited by Article 26 paragraph (2) of the Basic Agrarian Law. Foreign nationals are only allowed to use the land in Indonesia with the status of the rights which have a period of wear. During its development, the willingness of foreigners to own land property rights in Indonesia by using the name of an Indonesian citizen, by making an agreement before notaries. Property rights in land ownership certificate of proficiency level land is in the name of an Indonesian citizen, but with the agreement that was made in the presence of the notary, the land property rights are held by foreign nationals. The method used by notaries involved in the making of the agreement so that the foreign citizen has a right to the land belonging to the diverse, ranging from the lease agreement, acknowledgment of debt agreements, grants, and so on. The agreement set forth in the deed of agreement deed called counter letter, the agreement is contrary to the original agreement. Deed The legal basis of counter letter contained in Article 1873 Burgerlijk Wetboek. How is called the smuggling law.